2016
DOI: 10.1007/s11356-016-6699-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis, and antioxidant and antibacterial properties of chitosan-poly (vinyl alcohol) biodegradable films

Abstract: The development and characterization of biodegradable blend films based on chitosan and poly (vinyl alcohol) for possible use in a variety of biological activities are reported. Fourier transform infrared spectroscopy (FTIR) spectra of chitosan-poly (vinyl alcohol) (Ch/PVA) films showed characteristics peaks shifting to a lower frequency range due to hydrogen bonding between -OH of PVA and -NH2 of chitosan. The chitosan and PVA polymers presented good compatibility. The morphology study of chitosan and composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
83
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 41 publications
6
83
0
1
Order By: Relevance
“…Currently, scientists' interest is increasingly focusing on using biodegradable polymers for this purpose [1,2,[4][5][6]. Poly(vinyl alcohol) (PVA) and chitosan (Ch) [7][8][9][10][11][12][13] are the best known environmentally friendly polymers. PVA is a polymer that displays very useful functional characteristics, i.e., a high mechanical strength, photostability, and high gas barrier properties (especially in relation to oxygen) [4,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, scientists' interest is increasingly focusing on using biodegradable polymers for this purpose [1,2,[4][5][6]. Poly(vinyl alcohol) (PVA) and chitosan (Ch) [7][8][9][10][11][12][13] are the best known environmentally friendly polymers. PVA is a polymer that displays very useful functional characteristics, i.e., a high mechanical strength, photostability, and high gas barrier properties (especially in relation to oxygen) [4,13].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, poly(vinyl alcohol) is obtained through a hydrolysis reaction of poly(vinyl acetate) [4]. One of the most significant features of PVA is its hydrophilicity, which is the result of the presence of numerous hydroxyl groups in the main chain of the macromolecule [12]. Moreover, it should be mentioned that poly(vinyl alcohol) is characterized by unique properties, such as excellent film forming properties, high crystallinity, nontoxicity, and a remarkable chemical resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Many degradable materials have been applied on shell eggs to preserve the internal qualities, including synthetic polymers such as polysaccharides and proteins. [3][4][5][6][7][8] However, little information is available about the preservation effect of degradable coatings on SDEs. Wang et al [9] reported that composite coating based on nano-SiO 2 -modified polyvinylidene chloride could significantly (p < 0.05) reduce quality deterioration of SDEs such as weight loss, total volatile basic nitrogen (TVB-N), and total bacterial counts.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the composite films based on PVA and CHI had enhanced physical properties and high antioxidant activities. [7,8] Sodium alginate (SA) is a natural polysaccharide that can produce insoluble film by crosslinking of polyvalent metal cations. [10] Like CHI, SA has some special features, such as biocompatibility, chelating ability, and high hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%